Espresso Yourself: Are You A Coffeeholic? A Study of Customers Satisfaction on Costa Coffee in Malaysia - Ibrahim, Haslindar; Tunde, Odebunmi Abayomi; Abdul Hamid, Nur Amisha Nadia; Mahadir, Nur Anisa Najwa; Wahi Anuar, Nur Aqwa Badrisyia; Azamuddin, Nur Azera; Abimanyu, Naufal; Nisak, Nur Alifatun; Shinde, Ankita Sambhaji; Priyanka, Kanisetty (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Bringing to you London’s favourite coffee in Malaysia! The story began when the Costa brothers, Sergio and Bruno, decided to make a great cup of coffee as a part of everyday life in London. The impact of Covid- 19 has affected the entire world and the reliance on Costa Coffee apps has been doubled. Hence, the objective of this research paper is to study the satisfaction levels of customers from purchasing an espresso in the well- known cafe store, Costa Coffee. This study also aims to examine which factors that affect the customers’ satisfaction to snap up a specialty hand- crafted brew on Costa Coffee in Malaysia. Thus, the researchers also collected the data using a structured questionnaire survey and a sample of 150 Costa Coffee’s customers from Malaysia. The findings show that product quality, service quality, purchase intention and strategic location affecting the customers’ satisfaction of Costa Coffee. Overall, the data and results illustrates new insights and the claims of Costa Coffee regarding customers’ satisfaction that can help the company’s performance in the future.